Penerapan Akad Wadiah Pada Produk Simpanan Idul Adha Di Koperasi Syariah Masjid Al Arif Kota Bandung Dalam Perspektif Fatwa DSN MUI - Rudi, Rudiansyah (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2024)
The Shariah financial institutions in Indonesia are currently undergoing rapid and significant progress.This can be observed through the profiling of various financial institutions, both bank and non-bank, which actively contribute to the progress of the Indonesian economy.The research method used in this research is qualitative descriptive research method.Qualitative method is the method of research based on postpositive philosophy used to investigate on the conditions of natural objects to obtain data with a specific purpose of use on the product storage idol adha in KOPSYAR MAJTAMAS AL ARIF in using academic wadiah yad Trust compliance with the fatwa DSN MUI NO:86/DSN-MUI/XII/2012.The academic implementation of the academic Wadiah on KOPsYAR Majtamas AL ARif in the perspective of DSN- MUI can be said to be not in line with the principle of Shariah